In vivo biodistribution of nanoparticles. (July 2011) - Almeida, Joao Paulo Mattos; Chen, Allen L; Foster, Aaron; Drezek, Rebekah
Nanoparticles have potential applications in diagnostics, imaging, gene and drug delivery and other types of therapy. Iron oxide nanoparticles, gold nanoparticles and quantum dots have all generated substantial interest and their properties and applications have been thoroughly studied. Yet, metal-containing particles raise biodistribution and toxicity concerns because they can be quickly cleared from the blood by the reticuloendothelial system and can remain in organs, such as the liver and spleen, for prolonged periods of time. Design considerations, such as size, shape, surface coating and dosing, can be manipulated to prolong blood circulation and enhance treatment efficacy, but nonspecific distribution has thus far been unavoidable. Renal excretion of nanoparticles is possible and is size dependent, but the need to incorporate coatings to particles for increased circulation can hinder such excretion. Further long-term studies are needed because recent work has shown varying degrees of in vivo toxicity as well as varying levels of nanoparticle excretion over time. The interaction of these particles with immune cells and their effect on the innate and adaptive immune response also needs further characterization. Finally, more systematic in vitro approaches are needed to both guide in vivo work and better correlate nanoparticle properties to their biological effects.